OUTCOME OF PATIENTS WITH ST ELEVATION MYOCARDIAL INFARCTION (STEMI) BASED ON ADMISSION SERUM POTASSIUM LEVEL - Qayyum Malik, Sidra; Fatima Qayyum,; Masud Akhtar Malik,; Hamza Javed,; Ayub Khan, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Potassium levels play a significant role in cardiovascular patients, with hypokalemia and hyperkalemia having profound effects on the mortality rate. The aim of this study was to investigate the correlation of admission serum potassium levels and in-hospital mortality in patients suffering from acute ST-elevation myocardial infarction (STEMI). Methods: The study was conducted in the Department of Cardiology, Ayub Teaching Hospital Abbottabad, and involved 225 patients with STEMI who underwent thrombolysis with streptokinase. The serum potassium levels of patients were recorded at the time of admission, and its correlation was observed with the short-term outcomes, i.e., discharge to home versus those who did not survive during the hospital stay of 72 hrs. Results: The mean level of serum potassium at admission was 4.2 mmol/dL and 74.2% patients were discharged alive. T test indicated that a higher risk of death was associated with old age. No significant association between gender, serum potassium levels, systolic blood pressure, heart rate, and outcomes was seen. Logistic regression analysis further showed that age had a significant association with the outcome of death. Conclusion: In our study, age had a significant impact on predicting the mortality of patients with STEMI and whereas the serum potassium levels at the time of admission did not exhibit any significant predictive value. Further research is needed to elucidate the complex interplay of various factors in predicting mortality, to improve the management practices of AMI.